History of Nigeria - Burns, Alan. (London : Allen and Unwin, 1972)
This book is designed to give those who are interested in Nigeria, and particularly to such as are resident in the country, whether as missionaries, traders or officials, a short account of the history of its people and of their relations with the British Government.
(1 fold) of Nigerian map.
Includes bibliographical references and index.
osa 01/08/18
Loans
Keywords: History; Nigeria